ANALISIS PENDAPATAN DAN KONTRIBUSI PENDAPATAN PENGRAJIN GULA KELAPA TERHADAP PENDAPATAN KELUARGA DI DESA LOJEJER KECAMATAN WULUHAN KABUPATEN JEMBER - Siti Khotimah; Ati Kusmiati; Titin Agustina (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2014)
This research aims to know the: income disparity between the palm sugar craftsmen using the sap-sharing system and sugar-sharing system, factors that affect the income of palm sugar craftsmen, and palm sugar craftsmen income contribution on family income. The location of the research is determined by purposive method in the Lojejer Village Wuluhan Subdistrict Jember Regency. The research method used is descriptive method, comparative and analytical. Sampling method used is Disproportionate Stratified Random Sampling method. The Data used are the primary data and secondary data. Data analysis used in this study are:income analysis (π = TR – TC), multiple linear regression analysis (Y = a + b1X1 + b2X2 + b3X3 + b4X4 + b5X5 + b6 D + e), and proportions analysis (p = Pw/Pd x 100%). The results of this research indicate: (1) there are differences in palm sugar craftsmen income using the sap-sharing and sugar-sharing system. (2) factors that significantly influence to the income of palm sugar craftsmen using the sharing system the Lojejer Village Wuluhan Subdistrict Jember Regency, are: fuel costs (Rp), additional material costs (Rp), the selling price (Rp), the amount of production (Kg), labor (Rp), and the sharing system being used, (3) palm sugar craftsmens income contributions on family income in the Lojejer Village Wuluhan Subdistrict Jember Regency is medium, with a value of contribution revenue 69,53%.   Keywords: palm sugar, craftsmens, sharing system, income